Measuring the impact of the knowledge economy on achieving competitive advantage in developing countries - Mokhtar, Mohanad Abbas; Moussa, Adam Ahmed (Journal of Economic, Administrative and Legal Sciences, 2017)
This study discuss the issue of the knowledge economy and its role in achieving competitive advantage in the Developing Countries, by considering that organizations existence in an economy based on knowledge and how to achieve competitive advantage through what is available has a distinctive resources for this economy and how it can create this distinction effective facilitation of knowledge available in the organization .aimed to identify and define concepts related to knowledge and how to identify best techniques for the effective management of knowledge. The problem of study represented on role the knowledge economy to achieve competitive advantages and to identify reality knowledge economy to achieved advantages .• The research arrival many of results the most important knowledge considered crucial to achieve comprehensive development in today’s world and represents the information and communications technology, and modern science and technology as a technology Nano technology and biotechnology and space technology and other basic tools to achieve progress through the knowledge-based economy and about the real shift towards the best use of natural and physical resources. This includes the fundamental foundation of human development and basic-based economic and social development. The recommendations of study including the importance for focusing on scientific research related to the knowledge economy. Increasing procedures sticks the spending provision for the promotion of scientific research and innovation.